Entrepreneurial Marketing Program, Firm’s External Relationship and Export Performance of Indonesian Handicraft Sector - Munawar, Fansuri; Roespinoedji, Roeshartono; S. Brahmana, Sunardi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of entrepreneurial marketing program and firm’s external relationship toward export performance of the handicraft sector. The sample in this study was the owner or leader of the handicraft sector, comprising 72 respondents with a sampling technique using purposive random sampling. Data collection techniques by distributing questionnaires, interviewing, and recording documentation from respondents. The data analysis using the Structural Equation Model (SEM) based on Partial Least Square (PLS) with the tools Smart PLS 3.0. The results show that the effect of entrepreneurial marketing program toward firm’s external relationship is positive and significant. The role of entrepreneurial marketing program on performance is positive and significant. The effect of a firm’s external relationship toward performance is positive and significant. The role of firm’s external relationship as a mediator, the relationship between entrepreneurial marketing program toward performance, is positive and significant. This study also provides a solution to the owner or leader of the handicraft sector in maintaining long-term business, business growth, and performance.